The Hidden Realities of Discrimination from Patients: A Scoping Review of Healthcare Workers’ Experiences - Barned, Claudia; Nwafor, Akosua; Anderson, Melanie (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Discrimination in healthcare settings is a burgeoning area of applied inquiry and intervention. Existing research has focused on the experiences of patients as the targets of discrimination with less attention paid to patients as the source of discrimination. The main objective of this scoping review is to identify, explore and map the literature on the experiences of healthcare workers (HCWs) as targets of discrimination from patients and/or their family members. A scoping review of articles indexed in Ovid Medline, Ovid Embase, Ovid Emcare, and Web of Science Core Collection was conducted between March 2022 and June 2023. The results were summarized, coded and thematically categorized according to the aim. The review identified 173 articles that highlighted various forms of discrimination manifesting in a multitude of ways, including requests for, and refusals of specific HCWs based on social identity markers. The results suggest that there are significant barriers that prevent HCWs from reporting and responding to these incidents in efficient ways, resulting in an array of negative psychological ramifications. This review highlights core areas in need of greater attention in order to better support HCWs during challenging interactions with discriminatory patients. Institutional recommendations aimed at research and education efforts, learner experiences, policy writing, documenting and reporting, institutional culture, resources and support as well as the role of professional bodies, were identified. Evidence-informed work is needed in this area to ensure that policy-level changes are informed by the lived experiences of those enduring these incidents.